Wearable microstrip patch antenna for elderly healthycare monitoring - Ahmed, Mohamed Abdimalik (2021)
Recently, there is a growing demand of healthcare monitoring for elder people. Therefore, wearable antennas become the best solution to monitor elderly’s body. Fabric is considered the most suitable material for body wearable applications due to its flexibility this type of antenna textile or fabric based which has the characteristics of wearable microstrip patch antenna such as light weighted, easily attached to the body of senior person and low cost. A wearable microstrip patch antenna operating at single frequency 2.45 GHz had been designed. Therefore, the geometry of the patch antenna is 51 mm (L) × 56 mm (W) while the ground plane and substrate dimensions are 73 mm (L) × 73 mm (W). The substrate material used for this project is felt with a height of 1.1 mm and dielectric constant of 1.38 and copper for radiating element. The simulated return loss S11 of the microstrip patch antenna is -34.011 dB at 2.45 GHz, while the measured S11 is -19.507 dB at 2.44 GHz. In conclusion, the simulated SAR confirms that the antenna is wearable, with 0.4755 W/kg at 2.45 GHz. Furthermore, the bending effect of the antenna with radius from 36 to 126 mm and its SAR was analysed. The SAR value of the antenna was tested, based on flat and bended antenna to show the radiation effect on the human body phantom. The bended SAR value shows 0.702 W/kg at 2.45 GHz. The SAR values of both antennas are safe according to the International Commission on Non-Ionizing Radiation Protection (ICNIRP), European standard. The standard safe level is 2 W/kg for any 10 grams of tissue. The antenna performance was measured using Vector Network Analyzer. The simulated and measured results shown a good agreement only on the frequency but shows different results on the return loss.